(untitled) (Journal of the College of Basic Education, 2022)
Experiment had been done to study the affection, if mix nanomaterials with soil which prepared to produce barley (Hordeum vulgare) under several levels of humidity, the study included the grow and the it’s contents. The experience had been done by using partial way (slabs) that divided once and the design completely matrix Randomized Completely Block Design (RCBD) with three replications, the main plots watering that are (each day 3 & 6 & 9 & 12 &15) in the range of mixing the Nano materials with 1% , 2% , 3% , 4% , 5% by three replications, thus I have reached to the following results: 1- The Prolong duration of watering that was 15 days lead to Lack of specifications which were estimated and the watering raised for 12 days in the specifications Tillers & leaves (10.54 tillers/ plant) & (10.47 tillers/ plant) and the number of ears (10.33 ears/ plant ) the weight of the seeds (4.06 g/ plant ) and the weight of the Dry matter (8.60 g/ plant) and the Harvest Manual (47.20%). 2- The mixing of the agricultural soil with Nano mater led to enhance in growing of the plant and the good seed the range of mixing was 4% in the specification of plant a in weight & long , while the mixing 5% was giving result in long & weight and long of the shank and the ears of the plant. 3- We notice that the mixing is giving good results in major specifications with increasing the watering adding to the Agricultural soil with Nano Meter . 4-Simple regression coefficient was positive value, that means increasing the expected result for those features with increasing the nanomaterials , and it is refers to be growing under lack watering and lack moisture and can save water of irrigation.